The Effect of International Monetary Fund and World Bank Programs on Poverty - Easterly, William (World Bank, Washington, DC, 2014)
Structural adjustment - as measured by the number of adjustment loans from the IMF, and the World Bank - reduces the growth elasticity of poverty reduction. The author finds no evidence for structural adjustment having a direct effect on growth. The poor benefit less from output expansion in countries with many adjustment loans, than they do in countries with few such loans. By the same token, the poor suffer less from an output contraction in countries with many adjustment loans, than in countries with few. Why would this be? One hypothesis is that adjustment lending is counter-cyclical, in ways that smooth consumption for the poor. There is evidence that some policy variables under adjustment lending are counter-cyclical, but no evidence that the cyclical component of those policy variables affects poverty. The author speculates that the poor may be ill placed to take advantage of new opportunities, created by structural adjustment reforms, just as they may suffer less from the loss of old opportunities in sectors that were artificially protected before reform. Poverty's lower sensitivity to growth under adjustment lending, is bad news when an economy expands, and good news when it contracts. These results could be interpreted as giving support to either the critics, or the supporters of structural adjustment programs.